circ-1584 selectively promotes the antitumor activity of the oncolytic virus M1 on pancreatic cancer - Taofang Hao; Yuanyuan Li; Qianyao Ren; Ying Zeng; Leyi Gao; Wenbo Zhu; Jiankai Liang; Yuan Lin; Jun Hu; Guangmei Yan; Shuxin Sun; Jing Cai (Molecular Therapy: Oncology)
Pancreatic cancer is among the most challenging tumors to treat, and due to its immune tolerance characteristics, existing immunotherapy methods are not effective in alleviating the disease. Oncolytic virus therapy, a potential new strategy for treating pancreatic cancer, also faces the limitation of being ineffective when used alone. Elucidating the key host endogenous circular RNAs (circRNAs) involved in M1 virus-mediated killing of pancreatic ductal adenocarcinoma (PDAC) cells may help overcome this limitation. Here, we report that the oncolytic virus M1, a nonpathogenic alphavirus, exhibits different cell viability-inhibitory effects on different pancreatic cancer cells in the clinical stage. Through high-throughput circRNA sequencing, we found that circRNA expression varies among these cells. Further gain-of-function and loss-of-function experiments have shown that circ-1584 can selectively enhance the anti-pancreatic cancer effects of the M1 virus in vitro and in vivo. Additionally, circ-1584 may negatively regulate miR-578 to modulate the anti-pancreatic cancer effects of the M1 virus. Our findings lay the foundation for using circRNA as an adjuvant to enhance the M1 virus efficacy against pancreatic cancer.